Ответы и объяснения

  • Minsk00
  • почетный грамотей
2013-07-08T09:11:16+04:00

Преобразуем третью дробь

 1/(1+(1-b*a^(-1))/(1+b*a(-1)) = 1/(1+(a-b)/(a+b)) =1/((a+b+a-b)/(a+b))=(a+b)/(2a)

 

2a*корень( a^2-b^2)/(b^2(ab^(-1)+1)^2 =2a*корень(a^2-b^2)/(b^2(a^2b^(-2)+2ab^(-1)+1)) =

=2a*корень(a^2-b^2)/(a^2+2ab+1) =2a*корень(a^2-b^2)/(a+b)^2

 

2a*корень( a^2-b^2)/(b^2(ab^(-1)+1)^2 *1/(1+(1-b*a^(-1))/(1+b*a(-1)) = 

= 2a*корень(a^2-b^2)/(a+b)^2 * (a+b)/(2a) =корень(a^2-b^2)/(a+b)

 

((a+b)/(a-b))^(1/2) = (a+b)^(1/2)*(a-b)^(1/2)/(a-b) =(a^2-b^2)^(1/2)/(a-b)

 

((a+b)/(a-b))^(1/2)-2a*корень( a^2-b^2)/(b^2(ab^(-1)+1)^2 *1/(1+(1-b*a^(-1))/(1+b*a(-1)) =

=корень(a^2-b^2)/(a-b)-корень(a^2-b^2)/(a+b) =

= корень(a^2-b^2)(1/(a-b)-1/(a+b)) = корень(a^2-b^2)(2b/(a^2-b^2)) =

=2b/корень(a^2-b^2)